Australia, US torture and the power of international law. Issue 4 (2nd October 2019) - Barnes, Jamal
ABSTRACT: Australia cooperated extensively with the George W. Bush administration during the 'war on terror.' However, in doing so, Australia failed to condemn, and in some instances, condoned US torture and detention programs. Does Australia's conduct demonstrate a failure of international law and human rights to constrain Australia's actions? Although the Howard government was heavily criticised for failing to uphold human rights in the fight against terrorism, international law was not forgotten. This article argues that international law shaped Australia's cooperation with the US. Australia strategically used international laws to legitimise its cooperation with the US in the face of evidence of US torture. International law was not dismissed to pursue national security interests but used to legitimise Australia's security policies.